Multiple Comorbidities, Psychiatric Disorders, Healthcare Resource Utilization and Costs Among Adults with Essential Tremor: A Retrospective Observational Study in a Large US Commercially Insured and Medicare Advantage Population - Dingwei Dai; Ali Samiian; Joaquim Fernandes; Henriette Coetzer (Journal of Health Economics and Outcomes Research)
# Background Essential tremor (ET), the most common movement disorder, often impairs patients’ ability to perform activities of daily living, mental health, and quality of life.